2022
DOI: 10.2147/phmt.s351759
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan and Associated Factors of Peripheral Intravenous Cannula Among Hospitalized Children in Public Hospitals of the Gurage Zone, Ethiopia, 2021

Abstract: Background Peripheral intravenous cannulas are routinely used in hospital-admitted children requiring intravenous therapy. The majority of peripheral IVC lines are removed before completion of therapy due to cannula complications in children. Peripheral intravenous cannula securing is a painful procedure for children, so recognizing the variables associated with the peripheral intravenous cannula lifespan would help decrease the complications and increase the duration of cannula patency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
1
1
1
Order By: Relevance
“…Various studies on pediatric population reported the rate of PIVC complications within the range of 34% to 56% [ 7 ]. In this study, there is a high incidence of PIVC complications among admitted neonates and infants, which were observed in more than half of the participants (56.4%), and this result was slightly higher than the report of previous studies [ 14 , 15 , 18 ]. However, it was slightly lower than the result reported in Brazil [ 10 ].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Various studies on pediatric population reported the rate of PIVC complications within the range of 34% to 56% [ 7 ]. In this study, there is a high incidence of PIVC complications among admitted neonates and infants, which were observed in more than half of the participants (56.4%), and this result was slightly higher than the report of previous studies [ 14 , 15 , 18 ]. However, it was slightly lower than the result reported in Brazil [ 10 ].…”
Section: Discussioncontrasting
confidence: 69%
“…The most common anatomical site of cannula insertion was on the dorsum of the hand which is supported by various studies [8,14,17,18]. However, in Jerusalem, Israel the common anatomic site of insertion was the antecubital fossa [15].…”
Section: Discussionmentioning
confidence: 83%
“…Muitos dos medicamentos supramencionados são classificados como de alto risco para a ocorrência de complicações, quando administrados através de veias periféricas (27)(28)(29) devido ao potencial de hidrogênio (pH) menor do que 5 ou maior do que 9 não, assim como osmolaridade superior a 600mmOsm/L. (30) Tais características irritam o endotélio vascular da criança, predispondo-a à ocorrência de complicações locais associadas a TIV, infiltração, extravasamentos e depleção da rede venosa ao longo do período de hospitalização da criança, (27)(28)(29)(30)(31) demandando novas e repetidas tentativas de CIP.…”
Section: Discussionunclassified